Therapeutic effects of Isaria felina on postmenopausal osteoporosis: modulation of gut microbiota, metabolites, and immune responses - Xiaoyan Li; Chenhui Xue; Yongming Yang; Lili Zhao; Lixia Chen; Jing Wang; Lei Yan; Zan Meng; Xiaochen Qiao; Sujiao Liang; Xihua Yang (Frontiers in Immunology)
BackgroundThe intricate relationship between human health and gut microecology has emerged as a central theme in contemporary medical research. Postmenopausal osteoporosis, primarily driven by estrogen deficiency, remains a major health concern. Traditional Chinese herbal medicines have attracted significant interest for their promising role in osteoporosis treatment.MethodsThe effects of Isaria felina, derived from Cordyceps sinensis, on postmenopausal osteoporosis in rats are the focus of this study. Adult female Sprague-Dawley rats were categorized into control, postmenopausal osteoporosis (OVX), and Isaria felina-treated (IF+OVX) groups. Following a 12-week treatment period, various analyses, including micro-CT, histological assessments, 16S rDNA sequencing, untargeted metabolomics, flow cytometry, and ELISA, were performed.ResultsMicro-CT and histological assessments indicated significant improvements in bone loss and obesity control in OVX rats treated with Isaria felina. 16S rDNA sequencing revealed that Isaria felina corrected gut microbiota dysbiosis, particularly in the Bacteroides and Ruminococcus genera. Untargeted metabolomics highlighted alterations in nucleotide and lipid metabolism. Flow cytometry and ELISA analyses demonstrated that Isaria felina modulated the Th17/Treg immune balance, resulting in reduced levels of inflammatory cytokines IL-17 and TNF-α.ConclusionsThese findings indicate that Isaria felina mitigates bone loss in postmenopausal osteoporosis through modulation of gut microbiota and immune responses, underscoring its potential as a therapeutic agent for osteoporosis treatment.